A fõvárosi lakótelepek ingatlanpiaci helyzetének változása a rendszerváltás után (Szociológiai Szemle, 2024)
The paper presents research findings on changes in the property market position of the large housing estates of Budapest. During the last ten years the relative position of large housing estates has been decreasing, even faster, than it had before 1990. This trend was still not big enough to make these flats assailable. The result is, that the status of these housing estates has remained a somewhat middle-class one. The reason is, that the number of newly built flats continues to be very low in Budapest. That is why housing estates remain for certain groups of the middle class to be suitable places for living. When the speed of construction of new housing will be higher, some estates will face the danger of falling into slum-situation.